Pengaruh Pendapatan, Kesadaran Wajib Pajak, dan Modernisasi Sistem Administrasi Terhadap Kepatuhan Pajak Kendaraan Bermotor di Kabupaten Kediri 2024 - Erna Purwaningtyas; Badrus Zaman; Sigit Puji Winarko (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This research is motivated by the phenomenon of declining compliance levels of motor vehicle taxpayers in Kediri Regency in the last five years, despite the provision of various modernization services. Motor vehicle tax itself is one of the main sources of regional revenue that is very important in supporting development and financing public services. This study aims to determine the effect of income levels, taxpayer awareness, and modernization of the tax administration system on motor vehicle taxpayer compliance in Kediri Regency in 2024. The research method used is quantitative with a causality approach. The population in this study were all motor vehicle taxpayers in Kediri Regency, with a sample of 100 respondents selected using probability sampling methods and simple random sampling techniques. Data analysis was performed using multiple linear regression with the help of the IBM SPSS Statistics program version 30. The results of the study indicate that partially, the variables of income level and taxpayer awareness have a significant effect on motor vehicle taxpayer compliance, while the modernization of the tax administration system has no significant effect. However, simultaneously, all three variables have a significant effect on motor vehicle taxpayer compliance. These findings demonstrate the importance of increasing awareness and community economic empowerment in encouraging tax compliance. Based on these findings, it is recommended that local governments and relevant agencies improve tax education and maximize the use of modern tax services to encourage higher public compliance. Furthermore, the results of this study indicate that despite the implementation of modernized tax administration systems, non-technical factors such as income level and taxpayer awareness still have a greater influence on motor vehicle taxpayer compliance. This suggests that improved technology and administrative systems alone are not sufficient to significantly improve tax compliance.